INFEKSI PERIODONTAL SEBAGAI FAKTORRISIKO KONDISI SISTEMIK - Oedijani Santoso (Odonto : Dental Journal, 2019)
According to Riskesdas 2018 the prevalence of dental and oral diseases in Indonesia is still high (57.6%) and the most cases are caries and periodontal disease. Periodontal tissue infection is a local oral infection that can be a focal oral infection, and has a risk of affecting systemic conditions. Microorganisms, toxins and inflammatory reactions in infected periodontal tissues can spread systemically to other parts of the body, thatcan cause infections in the area or worsen existing conditions. Systemic conditions that can be affected by periodontal tissue infections including coronary heart disease / arterosclerosis, stroke, diabetes mellitus, pregnancy, chronic pulmonary obstruction, acute respiratory infections. The purpose of this literature review is to refresh about oral focal infection, as well as more convincing that periodontal infection was a risk factor for systemic conditions, in terms of inflammatory reactions.Influencing inflammatory reactions are inflammatory mediators, including interleukin (IL-1α, IL-β, IL-6, IL-8), tumor necotic factors (TNFα) and prostaglandin E2 (PGE2). Biological mechanisms support the role of periodontal infection as a potential risk factor for a number of systemic conditions.Future multidisciplinary research should better illustrate the role of periodontal infections in systemic health, so that the influence between periodontal infections and systemic conditions such as premature LBW, diabetes, cardiovascular and cerebrovascular diseases, and respiratory diseases will be increasingly proven